1998
DOI: 10.1111/j.1600-0897.1998.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Immunoreactive Cytokines in Women with Preeclampsia

Abstract: Elevated levels of TNF-alpha and IL-6 may contribute to the putative endothelial dysfunction of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
263
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(297 citation statements)
references
References 38 publications
25
263
2
7
Order By: Relevance
“…It has been hypothesized that placental ischemia and hypoxia during late pregnancy may contribute to maternal endothelial cell dysfunction by enhancing the synthesis of cytokines such as TNF-␣ (12,14). In support of the cytokine hypothesis, several studies have shown increased plasma levels of TNF-␣ during preeclampsia (14,39,66,70). However, some studies have shown no change in plasma TNF-␣ levels in preeclamptic women (22,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been hypothesized that placental ischemia and hypoxia during late pregnancy may contribute to maternal endothelial cell dysfunction by enhancing the synthesis of cytokines such as TNF-␣ (12,14). In support of the cytokine hypothesis, several studies have shown increased plasma levels of TNF-␣ during preeclampsia (14,39,66,70). However, some studies have shown no change in plasma TNF-␣ levels in preeclamptic women (22,29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models of PIH have proposed that a localized reduction in the uteroplacental perfusion pressure and the ensuing placental ischemia and hypoxia during late pregnancy trigger the release of vasoactive factors from the ischemic placenta into the systemic circulation, and that the released factors in turn cause systemic vascular changes and lead to increased vascular resistance and PIH (3, 7, 11-17, 21, 35, 41, 47). Although several placental factors have been suggested, a key role for plasma cytokines in the pathogenesis of PIH has been hypothesized (12,14,39,66). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers hypothesized that the inadequate remodeling of uterine arteries characteristic of preeclampsia is responsible for the focal ischemia and generation of pro inflammatory cytokines such as Interleukin-6 (IL-6) and tumor nrcrosis factor a (TNF-a) by the placenta [7][8][9]. IL-6 enhances endothelial cell permeability, aberrant angiogenesis and inhibits prostacyclin synthesis thereby modifying vascular physiology profoundly [10].…”
Section: Introductionmentioning
confidence: 99%